Bi2MoO6 hierarchical microflowers for electrochemical oxygen evolution reaction. (25th May 2021) - Rani, B. Jansi; Yuvakkumar, R.; Ravi, G.; Pannipara, Mehboobali; Al-Sehemi, Abdullah G.; Velauthapillai, Dhayalan
Abstract: Solvothermal Bi2 MoO6 hierarchical microflowers synthesis has been successfully attempted. Methanol, ethanol and isopropanol have been mediated to synthesize three kinds of Bi2 MoO6 hierarchical microflowers. Highly oriented (311) plane growth of orthorhombic Bi2 MoO6 hierarchical microflowers have been confirmed. Interstitial vacancies and its role on electrochemical activity have been extensively discussed. Electrode fabrication was constructively done by using Ni foam substrate. Half cell arrangement of each electrode in alkaline medium has been designed to measure the electrochemical activity towards water oxidation. High current density of 356 mA/cm 2 was afforded by Bi2 MoO6 hierarchical microflowers mediated by ethanol solvent during synthesis. Low Tafel slope value of 43 mV/dec has been reported to obtain 10 mA/cm 2 current density. Higher conductivity long with very good electron transportation has been achieved and is also adapted for 12 h long time stability test and achieved 86% of retention in its performance. Hence, optimally prepared Bi2 MoO6 hierarchical microflowers could be an efficient electrode for clean energy fabrication. Highlights: Bi2 MoO6 revealed high 356 mA/cm 2 current density in OER activity. Bi2 MoO6 revealed low 43 mV/dec overpotential to obtain 10mA/cm 2 . Achieved higher conductivity with good electron transportation. Bi2 MoO6 electrode achieved 12 h long time stability of 86% retention.